Reconstruction of whistling deformity using V-Y advancement flap after primary cleft lip repair - Notodihardjo, Sharon Claudia (J Surg Case Rep, 2021)
Whistling deformity often occurs after cleft lip primary repair, marked by deficiency of vermilion tubercle. The purpose of the surgery includes improving the appearance and function of the lip. Adequate amount of vermillion tubercle is necessary to fully cover the front teeth, produce lip seal while speaking consonant sound and balance the projection of face. Many techniques are known to repair whistling deformity from fat injection to Abbe flap. In our department, we use V-Y advancement flap. At certain cases, we repeat the procedure to maximize the result. This simple and less complication technique shows stable outcome during follow up. We recommend this technique because of the non-visible scar after surgery, applicable for unilateral and bilateral cleft lip case at various age, and possible to be done under general or local anesthesia.